Effects of Sidamanik Black Tea on Salivary Flow Rate, Total Protein, and Albumin Levels in Young Adults: An in Vivo Study - Ika Astrina; Ameta Primasari; Minasari; Filia Dana Tyaningsih (Dentika: Dental Journal, 2023)
Saliva is crucial in maintaining oral health, performing functions such as antibacterial activity, buffering, and ensuring tooth integrity. In this regard, black tea, a medicinal plant with potential anti-cariogenic agents, has been suggested to exert preventive effects against caries. Therefore, this study aimed to determine effects of black tea consumption on salivary flow rate, pH, as well as total protein and albumin levels in young adults. A pre-experimental design was used with a one-group pretest-posttest approach. The samples selected were 18 healthy young adults aged 18-25 years, with DMF-T scores of 1-5. Salivary flow rate, total protein, and salivary albumin were measured using a digital scale after a 5-minute interval, the bicinchoninic acid assay method, and the bromocresol green method, respectively. The results showed a significant increase in salivary flow, a substantial decrease in albumin, and an insignificant elevation in total protein. In conclusion, black tea manifested the capability to prevent caries by enhancing salivary flow and total protein levels. Furthermore, the impact in inhibiting bacteria activity depended on the presence of salivary albumin.